Investigation Of Cultural Literacy In Early Children Through An ATIK Learning Model - Azizah, Siti Nur; Zubaedah, Siti (IJIGAEd: Indonesian Journal of Islamic Golden Age Education, 2024)
The decline of local culture in Indonesia is due to the heavy influence of foreign culture. So that the younger generation prefers foreign cultures. The decline in local culture is found in early childhood in the present era. So the cultivation of cultural literacy needs to be instilled from an early age at the educational level through appropriate learning models. So that when they grow up, children have knowledge and love for local culture. This study aims to describe and describe how to plan for planting cultural literacy and implementing cultural literacy in early childhood through the ATIK model at RA Bustanul Ulum Jayasakti. The research methodology is using a descriptive qualitative approach, the research location is at RA Bustanul Ulum Jayasakti, Central Lampung. This study used three research subjects, namely the principal and two class teachers. The results of the research conducted were that the RA Bustanul Ulum institution carried out planning in instilling cultural literacy in early childhood through three planning stages, namely planning for selecting activities, planning for budget costs and planning for determining activity schedules. The activities chosen in cultivating cultural literacy through the ATIK model are coloring pictures of traditional cultural clothes, traditional dances, and habituating good manners. With different activity schedules and costs incurred using BOP funds. While the implementation of these activities uses the ATIK model with 3 stages, namely children observing, imitating and doing. Cultivating literacy through careful planning and using the ATIK model makes the goal of cultural literacy achieved